Two chiral cadmium carboxylate framework isomers generated by spontaneous resolution: synthesis, structures and properties. Issue 2 (17th January 2019) - Chen, Yang-Yang; Tan, Chunhong; Song, Li-Ping; Zhou, Juan; Zeng, Qiongyao; Xie, Rui; Wang, Xiao-Feng
Abstract: Two three-dimensional (3-D) chiral coordination polymers, [Cd(NDC)(DMF)]n (1L and1D : H2 NDC = 1, 4-naphthalenedicarboxylic acid and DMF = N, N ′-dimethylformamide), have been synthesized by introducing the rigid achiral dicarboxylic acid ligand under solvo-thermal conditions, without chiral template or additives. Both chiral Cd-CPs were characterized by single crystal X-ray crystallography, and structural analysis indicates that1L and1D are enantiomers based on the zigzag [Cd(COO)2 (DMF)]n rod secondary building units, featuring the left- or right-hand 21 Cd-O-C-O-Cd helix chains and left- or right-hand 41 screw [Cd(NDC)]n columns, respectively. The FT-IR, TGA, powder X-ray diffraction and solid-state luminescence of1 have been investigated. It is intriguing that the evidence from the circular dichroism spectroscopies confirms enantiomeric excess in the whole spontaneous resolution crystallization. Graphical Abstract: